A new strong ground motion model for predicting Peak Ground Acceleration (PGA), pseudo-acceleration spectra and displacement spectra in Iran - A.R. Hajipour; H. Moghaddam (مهندسی عمران شریف)
Due to the inelasticity of the ground and geometric expansion, seismic waves are reduced by moving away from the center of wave propagation, which is called the attenuation of seismic waves. Therefore, the ground motions that occur at the site of the structures are different from the ground motions that are emitted from the source. The upcoming study investigates the attenuation of seismic waves in the geographical area of Iran based on the accelerogram data of Iran. In this study, a new ground motion model (GMM) for Iran is developed to estimate peak ground acceleration (PGA), pseudo-acceleration spectral values (PSA) in 2, 5, and 10 percent damping, and displacement spectral values (Sd) at 21 oscillator periods ranging from 0.04 s to 4 s. The displacement spectra considered in this research are those with a constant resistance-to-weight ratio, which includes both elastic and inelastic displacement types. Also, the considered resistance-to-weight ratios include five ratios from 0.05 to 0.3. The database of this study consists of 659 records of 115 shallow crustal mainshocks that occurred in Iran from 1976 to 2022 with a magnitude range of 5≤Mw≤7.4 and an epicentral distance range of 0 to 200 km. Random-effect coefficients were defined in the mixed-effect regression model for regional differences among the five regions of the Iranian plateau, and no statistical differences were detected among these regions. The effects of the site soil's nonlinear response are considered in the developed GMM using the VS30 parameter (average shear wave velocity in the upper 30 meters of the soil profile). The residuals of the proposed GMM are decomposed into three between-event, site-to-site, and event-site-corrected components, and their distributions are examined against the predictor variables. The distribution of residuals obtained showed no significant bias for the developed GMM. The output of this research is a GMM for Iran, which can be used to estimate the spectrum of pseudo-elastic acceleration and the spectrum of elastic and inelastic displacement.